A retrospective analysis of climate adaptation strategies and implications for food and nutrition security among small-scale farmers in South Africa - Kori, D. S.; Zhou, L.; Sibanda, M. (Frontiers in Sustainable Food Systems, 2023)
With the ever-increasing climate change, actions to reduce its negative impact while improving food and nutrition security are critical. This review is a retrospective analysis of climate adaptation strategies and implications for food and nutrition security among small-scale farmers in South Africa. The review used bibliometric analysis and Preferred Reporting Items for Systematic Reviews and Meta-Analysis to track research on implications of adaptation on food and nutrition security, identify adaptation strategies with implications on food and nutrition security and discuss the implications. The analysis shows a steady growth in the research field; however, whether the pace will accelerate the achievement of Sustainable Development Goal 2 by 2030 is unknown. Institutional research collaboration is notable, although weak. The co-occurrence of keywords reflects Climate-Smart Agriculture and food and nutrition linkages, emphasizes the importance of farmers’ perceptions on adopting measures to enhance food and nutrition security and illustrates the risk-vulnerability-resilience nexus. Adaptation measures with implications on food and nutrition security are varied, ranging from individual efforts to government-led initiatives. We recommend strengthening institutional research collaboration to accelerate the pace towards achieving zero hunger, food security and nutrition by 2030. It is also important to have an inclusive policy framework that addresses farmers’ adaptation needs.